Confronting AIDS : public priorities in a global epidemic - World Bank. (Oxford ; New York : Published for the World Bank [by] Oxford University Press, 1999)
Confronting AIDS is a strategic document, written to inform and motivate political leaders, policymakers, and development specialists to support the public health community, concerned civil society, and people living with HIV in dealing with this devastating disease.
Includes bibliographical references (p. 341-365).
rpm 21/09/16, ijb 20/02/2019
Loans
Keywords: AIDS (Disease); AIDS (Disease) -- Prevention -- Government policy